Patients’ Beliefs Regarding the Causes of Hypertension and Treatment Adherence as Predisposing Factors for Complications and Uncontrolled Blood Pressure - Nidhal Awad Obaid Alibraheemi (International Journal of Medical Sciences And Clinical Research, 2026)
Background: Hypertension is a highly prevalent non-communicable disease and a leading risk factor for cardiovascular morbidity and mortality. Despite effective treatments, blood pressure control remains suboptimal globally, partly due to patient beliefs and poor adherence, which contribute to the development of complications. Misconceptions about the causes and management of hypertension are particularly common in low- and middle-income countries. Aim of the study: To identify patients’ misconceptions about hypertension which may increase the risk of complications. Patients and Methods: A prospective cross-sectional study was conducted at Karbala Health Directorate primary health care centers, over a ten-month period. Two hundred adult patients with hypertension attending the primary health center were included. Data were collected using a structured questionnaire addressing sociodemographic characteristics, clinical history, beliefs about hypertension, and adherence to therapy assessed by the Modified Morisky Medication Adherence Scale. Blood pressure control and the presence of complications were recorded. Statistical analysis was performed to explore associations between patient beliefs, adherence, blood pressure control, and complications. Results: The mean age of participants was 54.3 years, with 52% male and 48% female. Misconceptions were widespread, with 60 % of patients believing stress was the main cause of hypertension, 45 % attributing it to blood viscosity, and 38 % to dietary fat intake. Only 40 % of patients achieved controlled blood pressure. High adherence to therapy was observed in 28 % of patients, medium adherence in 34 %, and low adherence in 38 %. More than half of the participants (56 %) experienced hypertension-related complications, most commonly kidney problems (22 %), heart attacks (18 %), and heart failure (16 %). Patients with low adherence were significantly more likely to have uncontrolled blood pressure and complications compared with those with high adherence (p